Implementasi Metode AHP dan SAW pada Sistem Informasi Data Penduduk Desa Sebente untuk Penentuan Prioritas Bantuan Sosial - Valenstina Salira Ndoe; Shanti Thomas (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Social assistence distribution is one of the government’s efforts to improve the welfare of communities inneed. The process of determining social assistance recipients must be carried out accurately so that the aid can be distributed to individuals who are truly eligible. Haowever, in Sebente Village, the process of selecting soscial assistance recipients is still conducted manually, which requires considerable time and has the potential to create subjetive in deciision-making. The study aims to develop a Decision Support System (DSS) that can assist the village government in determining the priority of social assistance recipients objectively, transparently, and accurately. The methods used in this study are the Analytical Hierarchy Proses (AHP) and dan Simple Additive Weighting (SAW. The AHP method is employed to determine the weights of criteria based on their level of importance, while the SAW method is used to rank prospetctive social assistance recipients. The criteria applied in this study include income, number of dependents, housing, conditions, occupations, and assets. The system was developed as a web-based applications using PHP as the programming language and MySQL as teh database management system. The result of the study indicate that the AHP method producet the higets criterion weight for income, with a value of 0,49, and generated a Consistency Rasio (CR) of 0,064, demonstrating that the pairwise comparison matrix was consisten. Furthermore, the SAW method successfully ranked prospective soscial assistance recipients based on the highest preverence values. The developed system can assist Sebente Village officials in accelerating the selection process of social assistance recipients, improving the objectivity of assessments, and producing more effective and accurate decisions.